Disaster Education: A Survey Study to Analyze Disaster Medicine Training in Emergency Medicine Residency Programs in the United States. Issue 4 (20th March 2017) - Sarin, Ritu R.; Cattamanchi, Srihari; Alqahtani, Abdulrahman; Aljohani, Majed; Keim, Mark; Ciottone, Gregory R.
Abstract: Background: The increase in natural and man-made disasters occurring worldwide places Emergency Medicine (EM) physicians at the forefront of responding to these crises. Despite the growing interest in Disaster Medicine, it is unclear if resident training has been able to include these educational goals. Hypothesis: This study surveys EM residencies in the United States to assess the level of education in Disaster Medicine, to identify competencies least and most addressed, and to highlight effective educational models already in place. Methods: The authors distributed an online survey of multiple-choice and free-response questions to EM residency Program Directors in the United States between February 7 and September 24, 2014. Questions assessed residency background and details on specific Disaster Medicine competencies addressed during training. Results: Out of 183 programs, 75 (41%) responded to the survey and completed all required questions. Almost all programs reported having some level of Disaster Medicine training in their residency. The most common Disaster Medicine educational competencies taught were patient triage and decontamination. The least commonly taught competencies were volunteer management, working with response teams, and special needs populations. The most commonly identified methods to teach Disaster Medicine were drills and lectures/seminars. Conclusion: There are a variety of educational tools used to teach Disaster Medicine in EM residencies today, with a larger focus on the use of lectures and hospital drills. There is no indication of a uniform educational approach across all residencies. The results of this survey demonstrate an opportunity for the creation of a standardized model for resident education in Disaster Medicine. RR Sarin, S Cattamanchi, A Alqahtani, M Aljohani, M Keim, GR Ciottone .Disaster education: a survey study to analyze disaster medicine training in emergency medicine residency programs in the United States .Prehosp Disaster Med .2017 ;32 (4 ):368 –373 .